Impact of non-genetic factors on severe cutaneous adverse reactions and associated mortality in ESRD patients: Advancing clinical guidance - Smaha, Katlyn M; Talebi, Nadia N; Waller, Jennifer L; Baer, Stephanie L; Bollag, Wendy B (The American journal of the medical sciences, 2025)
In end-stage renal disease (ESRD), reduced renal function affects medication response and clearance, increasing risk of adverse drug reactions. Renal disease is a risk factor for poor prognosis in severe cutaneous adverse reactions (SCARs). The effects of SCARs in ESRD patients are less understood. This retrospective analysis of the United States Renal Data System (USRDS) evaluated whether SCARs are an independent risk factor for mortality in ESRD patients, controlling for demographic and clinical factors, including malnutrition, sepsis, pneumonia, secondary autoimmune conditions and Charlson Comorbidity Index (CCI). We examined whether Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) or drug reaction with eosinophilia and systemic symptoms (DRESS) was associated with all-cause mortality in subjects enrolled in the USRDS from 2005 to 2018. Patients with DRESS were more often female (OR = 1.37), with catheter (OR = 1.08) or graft (OR = = 1.15) access and a higher CCI (OR = 1.21). Those with SJS/TEN were more likely to be black (OR = 2.43) or other race (OR = 2.06) and female (OR = 1.55), with catheter access (OR = 1.36) and a higher CCI (OR = 1.18). DRESS and SJS/TEN were associated with higher risk of malnutrition (OR = 1.64, OR = 2.61), sepsis (OR = 1.93, OR = 3.38), pneumonia (OR = 1.82, OR = 1.80), and secondary autoimmune conditions (OR = 1.47, OR = 1.47). Patients with DRESS (HR = 2.05) or SJS/TEN (HR = 3.12) had increased mortality across 12 months following diagnosis. Increasing age (HR = 1.04), hemodialysis (HR = 1.76), catheter (HR = 2.58) or graft (HR = 1.52) access, malnutrition (HR = 1.07), and sepsis (HR = 1.26) increased mortality risk. ESRD patients' risk for SCARs varied by age, race, sex, comorbidities, and dialysis modality. Patients with a SCAR had increased mortality across 12 months following diagnosis.